Application of Ludo Modification Game to Intoduce the Concept of Early Social Studies on Children Age 5-6 Years in Dharma Wanita Kindergarten Ngawen Pati - Yadi, Dwi Safitri; Diana, Diana (BELIA: Early Childhood Education Papers, 2018)
The concept of social studies is one of the knowledge that must be introduced in early childhood. One of methods that can be done to introduce to children the concept of social studies is through play activities. Through the ludo game modifications, can be expected to help children in recognizing the concept of social studies. The problem of this research is whether there is a difference of understanding of learning concept of early social studies through ludo modification game in children aged 5-6 years. This study aims to determine the difference in understanding the concept of learning early social studies through ludo game modification activities in children aged 5-6 years. This research was conducted in Dharma Wanita Kindergarten in Ngawen Pati by using Pre-experimental Design with One Group Pretest-Postes Design approach. The samples that used are children aged 5-6 years by 30 children. Sampling technique in this research is Purposive Sample technique. The data analysis method was used Independent Sample t-Test method. The data shows an increase in the mean value from 90.87 to 122.97. The magnitude of the increase is 32.1. Based on the result of calculation using Paired Sample t-Test, the value of t table> t count> t table, that is (- 2.045> -16,146 or 16,146> 2,045), with Sig = 0.000 or Sig. (2-tailed) <0.05 so that ð»ð‘Ž is accepted and ð»0 is rejected. Therefore, it can be concluded that there is a significant difference in understanding the concept of social studies children 5-6 years of Dharma Wanita Kindergarten in Ngawen Pati after using the media game ludo modification.